1998
DOI: 10.1046/j.1365-2990.1998.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of cyclin A in astrocytic tumours

Abstract: Cyclins are important regulators of the cell cycle; there is increasing evidence that some cyclins are positively involved in carcinogenesis. Amplification and translocation of the cyclin genes and overexpression of their mRNAs and proteins have been observed in a variety of tumours. We studied cyclin A protein in astrocytic tumours by immunohistochemical analysis. Immunohistochemistry with microwave antigen retrieval was carried out on formalin fixed, paraffin embedded material from 15 glioblastomas (WHO grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…Frequency of cyclin A expression has been found to be associated with increasing grade of astrocytoma in a previous study [38], with very similar LIs to the findings we describe. On the other hand, we found all tumours in our study to express cyclin A, regardless of histology or grade, compared to expression in only 66% of cases in the previous study [38]. It is possible that technical and/or other limitations in the previous study were responsible for the observation that 34% of gliomas appeared to have no cells in S‐phase of the cell cycle.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Frequency of cyclin A expression has been found to be associated with increasing grade of astrocytoma in a previous study [38], with very similar LIs to the findings we describe. On the other hand, we found all tumours in our study to express cyclin A, regardless of histology or grade, compared to expression in only 66% of cases in the previous study [38]. It is possible that technical and/or other limitations in the previous study were responsible for the observation that 34% of gliomas appeared to have no cells in S‐phase of the cell cycle.…”
Section: Discussionsupporting
confidence: 91%
“…Previous investigations have shown a correlation between outcome in glial tumours and expression of individual cell cycle markers such as Ki67, cyclin D1 and cyclin A [36–40]. Indeed, Mcm‐2 has been shown previously to provide prognostic information in a small series of oligodendrogliomas [27].…”
Section: Discussionmentioning
confidence: 99%
“…Over‐expression or deregulated expression of cyclins A and B can contribute to the development of neoplastic disorders, either directly or indirectly by causing the phosphorylation of oncogenic products by a cyclin‐dependent kinase 27 . In brain tumours, there have been several studies about cyclin A in astrocytic tumours, 8,9 but in oligodendrogliomas, none was found in an extensive Medline search. In our study, we found that cyclin A played an important role in malignant transformation of this tumour and the LI of cyclin A in low‐grade oligodendrogliomas and high‐grade oligodendrogliomas was 1.18 ± 0.98 versus 4.65 ± 1.99, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies concerning various cyclins in non‐oligodendroglial glial tumours 8,9 and the usefulness of Ki67 in oligodendrogliomas 10–14 have been reported. However, only a couple of studies of cyclin A and cyclin D in oligodendroglioma can be found in a Medline search 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Expression of cyclins and Cdks are frequently increased in high-grade astrocytomas, often through amplification of gene dosage [122,166,[168][169][170][171][172][173]. However, these alterations are uncommon in low-grade gliomas, such as pilocytic astrocytomas [174].…”
Section: Cell Cycle and Brain Tumorsmentioning
confidence: 99%